EKSISTENSI PENGADILAN HAK ASASI MANUSIA TERHADAP PENYELESAIAN KASUS-KASUS PELANGGARAN HAK ASASI MANUSIA BERAT DI INDONESIA - Walidain, M. Ahsanul; Effendi, Erdianto; ', Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Since the end of the Cold War, marked by the collapse of one of the superpowers, namely the Soviet Union, it is a global issue switch from communism and conflict between the Western bloc and the Eastern bloc, to a new problem, namely the problem of human rights, environmental issues, and problems of trade liberalism. Homeland as part of the international community, can not be separated from the issue of human rights wave that hit almost all countries in the world. Sendirir in Indonesia, particularly in East Timor, based on the record Violations Investigation Commission (KPP HAM) has occurred 670 cases of human rights violations, which occurred between January and December 1999. The gross human rights violations that occurred in East Timor in the form of, the murder of hundreds of people of Timor east, torture, intimidation, rape, forced deportations, and others. As more and continuation of various crimes against human rights, then the five UN ambassador immediately flown to Jakarta to ask the Indonesian government to permit the entry of an international force to East Timor. However the Indonesian side rejected because it was considered as an intervention against sovereignty. Finally in 2000 was born the Law on Human Rights Court that at the time somewhat forced to avoid the slide of the Army General in the vortex of international criminal justice, namely Law No. 26 Year 2000 on Human Rights Court.above explanation, the study focused on how the existence of the Human Rights Court Against Settlement Cases Serious Human Rights Violations in Indonesia. The aim of this study are: first, to determine the existence of the Court of Human Rights in examining and deciding various violations of human rights that have occurred in Indonesia. Second, to look for problems or obstacles in the human rights court to thoroughly investigate serious human rights violations in Indonesia, and the research also aimed to look for actions that must be performed by state officials, government and the community to the human rights court can run as it should.In this legal study, researchers used a type of normative legal research. The research method in this paper is the research library (library reserch) are taken from various sources of law. Source of data used primary data, secondary data, and tertiary.this study is that the existence of Indonesian human rights court is not very good in heavy thoroughly investigate human rights violations in Indonesia, which can be seen from the results of decisions and events that occurred during the trial. While the problems of poor existence of the Human Rights Court is there in terms of the substance of the law in this regard is Act No. 26 of 2000 on Human Rights Court, law enforcement and legal culture of Indonesian society.Keywords: Existence - Serious Human Rights Violations - Indonesian Human Rights Cour